Interpretitve principles of stage implementation of Frank Marten’s Oratorio “The Magic Potion” in the Theater St. Gallen - Kozyk, Daria (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. Among the stylistic diversity of composer and vocal practice of the 20th century, which has been thoroughly studied in domestic musicology, the practitioner finds several little-known personalities of the music culture of Western Europe. Amid such names lies the figure of the Swiss composer Frank Martin (1890–1974). He is the author of oratorios Golgotha, In terra pax, Requiem, orchestral and chamber works. His works came from a period of active innovation and experimentation in music. The composer's writing is marked by the synthesis of dodecaphony and the classical functional tonality' system. The analysis of the embodiment of contemporary oratorio-opera on the stage is always of particular interest for contemporary interpretation. This also applies to the staging of F. Martin's works, which are not widely known, and therefore have not been studied at all. Thus, the relevance of the topic lies in the conceptualization of F. Martin's insufficiently explored oratory work, which deserves to be introduced into the scientific circulation of domestic musicology and the study of staging. Main objective(s) of the study is to substantiate the concept F. Marten’s «The magic potion» in the aspects of genre-stylistic and performing tasks of its stage realization. The object of study is F. Martin's vocal and choral works; its subject is the stylistic principles of the oratorio-opera The Magic Potion in the aspect of performing tasks of its stage realization. The methodology. Research methods are determined by the material and subject of research: historical — reveals the features of the context of socio-cultural life of Switzerland in the war and postwar years; biographical — contains information about the life and work of the composer; function and structure method — helps to determine the intonation structure of the work through the functions of i m t; stylistic — reveals the specifics of the artist's thinking «as an artistic unity» (according to S. Skrebkov). Results and conclusions. Using the original source of the medieval epic — the legend of Tristan and Isolde, — the composer sharpened the conflict of literary model (Joseph Bédier, Roman de Tristan et Iseut), taking the narrative into a more realistic channel that is focused on the feelings of the heroes. Following the tradition of ancient tragedies, in which the choir played the role of the engine of the plot, the composer transferred the function of narrative to an ensemble of twelve voices, part of which are the main characters of the plot. F. Martin designed The Magic Potion as a secular oratorio, without the ability to perform music as a grand opera, but did not exclude the possibility of a stage embodiment where the main characters would be portrayed by soloists that don't belong to the choir. An in-depth analysis of one of the contemporary stage performances of the St. Gallen creative team has shown current trends in contemporary vocal performance. Opera as a form of art attracts both the public and engaged composers and performers around the world. The contemporary opera genre demands particular challenges for composers, performers and producers, as well as opera intendants. The study of the complex genre structure of the work not only in the aspect of musicological analysis by the score, but also in the aspects of its stage embodiment (that is, the performing version of the oratory score) constitutes a scientific relevance and significance of the researched topic.